Pengaruh Firm Size dan Opini Audit terhadap Audit Delay: Studi Kasus Perusahaan Manufaktur Sektor Barang Konsumsi Terdaftar di BEI Tahun 2021–2023 (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the impact of firm size and audit opinion on audit delay, with Return on Assets (ROA) and affiliation with Big Four Public Accounting Firms (KAP) as control variables. Audit delay in financial statements can reduce the relevance of information and pose risks to investors and regulators, making reporting efficiency an important factor to consider. The sample used in this study includes 45 manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the period of 2021–2023, with a total of 135 observations. This study employs panel data regression analysis and applies the Breusch-Pagan and Hausman tests, which determine the Random Effect Model (REM) as the best model, with adjustments for robust standard errors. The results indicate that audit opinion, ROA, and affiliation with Big Four KAP have a significant negative effect on audit delay, while firm size does not show a significant impact. Simultaneously, the independent variables in this study influence audit delay, supporting Positive Accounting Theory and Signaling Theory. These findings have important implications for improving reporting efficiency, better audit quality, and more effective regulatory oversight.